2016
DOI: 10.1097/j.pain.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture reduces pain in pediatric kidney biopsies: a randomized controlled trial

Abstract: Evaluate laser acupuncture as an adjuvant therapy in pain management during percutaneous kidney biopsy procedure in children and adolescents. This prospective, double-blinded, randomized controlled trial enrolled patients aged 7-26 years admitted to a children’s hospital for percutaneous kidney biopsy. Patients received laser acupuncture to treatment points (acupuncture group) or sham points (control group) prior to the procedure. Laser delivered a dose of 42 J/cm2 over 10 acupoints. Patients and parents rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“… 17 Oates et al., 2017 7–26 year old 69 Procedure pain in kidney biopsy Two-arm RCT Adjunctive laser acupuncture significantly improved pain after pediatric percutaneous kidney biopsies. 14 Pour et al., 2017 6–12 year old 120 Venipuncture pain Three-arm RCT Acupressure at the Extra −1 (Yintang) and the PC8 (Laogong) was as effective as topical anesthesia cream in alleviating children's venipuncture pain. 15 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 Oates et al., 2017 7–26 year old 69 Procedure pain in kidney biopsy Two-arm RCT Adjunctive laser acupuncture significantly improved pain after pediatric percutaneous kidney biopsies. 14 Pour et al., 2017 6–12 year old 120 Venipuncture pain Three-arm RCT Acupressure at the Extra −1 (Yintang) and the PC8 (Laogong) was as effective as topical anesthesia cream in alleviating children's venipuncture pain. 15 …”
Section: Resultsmentioning
confidence: 99%
“…This report evaluates research in pediatric acupuncture and pain management, in which approximately 55% of the selected articles were related to procedural pediatric pain management. The pediatric procedures included infant heel lancing, 3 , 4 , 7 , 8 , 9 ,nsillectomy 10 , 11 and dental-related, 12 myringotomy tube surgery, 13 kidney biopsy, 14 ventipuncture, 15 and endoscopic pre-procedural anxiety. 16 Collectively, these studies researched how acupuncture could lead to the reduction of post-operative pain, emergence irritation, procedural time, and infantile crying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, Oates et al found improvement of self-reported pain scores as well as the associated hemodynamic changes. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a gentle treatment tool, yet it is a relatively new research field in children and neonates. 31,32 Acupuncture treatment for pain in the paediatric population has been investigated in several studies, including headache, abdominal pain, fibromyalgia, juvenile arthritis, complex regional pain syndrome, cancer pain and perioperative pain. 33 In most cases, acupuncture has demonstrated a pain relieving effect and good acceptance by patients and parents, so it has been suggested as a safe and cost-effective treatment modality for paediatric pain.…”
Section: Discussionmentioning
confidence: 99%